Pengaruh Pemasaran Media Sosial dan Kesadaran Merek Terhadap Minat Pembelian Pada Bisnis (Studi Kasus Pada Konsumen @Palett.es) - Reisi Nisrina Octaviani; Bertadi Nurseno (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aims to determine the effect of social media marketing and brand awareness on purchase intention in the @palett.es business. The research method used is a quantitative method with data collection through questionnaires. The population in this st udy are consumers @palett.es. The sampling technique in this research is non -probability sampling with purposive sampling method using the formula from Hair et.al. that takes at least 5 times the number of question items contained in the questionnaire. The sample obtained is 120 respondents (24x5). The data analysis used in this study is multiple linear regression analysis with the help of the IBM SPSS Statistics 25 program. The results show that: (1) social media marketing has a significant positive effect on purchase intention with a value of 21.3%; (2) brand awareness has a significant positive effect on purchase intention with a value of 31.4%; and (3) social media marketing and brand awareness simultaneously have a significant positive effect on purchase intention with a value of 52.7%, with the remaining 47.3% being the influence of other factors not included in this study.